2020
DOI: 10.1021/acs.jmedchem.9b01154
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Compounds Bearing a Dipyrido-Pyrimidine Scaffold Acting as Novel Human and Insect Pest Chitinase Inhibitors

Abstract: Chitinases not only play vital roles in the human innate immune system but are also essential for the development of pathogenic fungi and pests. Chitinase inhibitors are efficient tools to investigate the elusive role of human chitinases and to control pathogens and pests. Via hierarchical virtual screening, we have discovered a series of chitinase inhibitors with a novel scaffold that have high inhibitory activities and selectivities against human and insect chitinases. The most potent human chitotriosidase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 60 publications
1
47
0
Order By: Relevance
“…24 Notably, the compound bearing a dipyrido-pyrimidine scaffold also showed potent inhibitory activity toward Of Chi-h. One of the compounds ( 16) inhibited Of Chi-h, with a K i value of 9 nM, which is the most efficient inhibitor toward insect chitinases thus far. 30 The crystal structure of Of Chi-h in complex with compound 16 revealed that the dipyridopyrimidine moiety bound at the +1 and +2 subsites and was sandwiched by two conserved tryptophans Trp268/Trp389 (Figure 3F). The 3-pyridinylmethyl carboxamide moiety extended toward the −1 subsite in close proximity to the catalytic residues.…”
Section: Development Of Small Molecules Targeting Insect Chitinasesmentioning
confidence: 99%
“…24 Notably, the compound bearing a dipyrido-pyrimidine scaffold also showed potent inhibitory activity toward Of Chi-h. One of the compounds ( 16) inhibited Of Chi-h, with a K i value of 9 nM, which is the most efficient inhibitor toward insect chitinases thus far. 30 The crystal structure of Of Chi-h in complex with compound 16 revealed that the dipyridopyrimidine moiety bound at the +1 and +2 subsites and was sandwiched by two conserved tryptophans Trp268/Trp389 (Figure 3F). The 3-pyridinylmethyl carboxamide moiety extended toward the −1 subsite in close proximity to the catalytic residues.…”
Section: Development Of Small Molecules Targeting Insect Chitinasesmentioning
confidence: 99%
“… For the future clinical candidate, we decided to focus our work on hCHIT1/hAMCase inhibitors and progress lead compound 3 . The independent, very recent publication on m- and hCHIT1 selective inhibitor and its antifibrotic activity in bleomycin induced lung fibrosis model in mice was reported by Jiang et al…”
Section: Resultsmentioning
confidence: 99%
“…A hierarchical virtual screening strategy was used as described previously 13 , 27 , 29 . First, structural analogues to active hits were identified from a subset of commercially available compounds from ZINC database 30 employing substructure search and shape similarity calculations.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of nematode chitinases indicates that they may be promising nematicide targets for the development of small-molecule inhibitors for nematode pest control 12 . Many GH18 chitinase inhibitors with diverse scaffolds have been reported so far, and some showed potential applications as antifungal agents, pesticides, and drugs 6,[13][14][15] . However, the inhibition of nematode chitinases is rarely studied, and only few inhibitors have been reported to be effective on nematode chitinases, including allosamidin, closantel, b-carboline, and 4-hydroxy-1,2,3-triazoles.…”
Section: Introductionmentioning
confidence: 99%